HUBUNGAN ANTARA PENGETAHUAN KELUARGA DAN DUKUNGAN KELUARGA DENGAN KEJADIAN STROKE PADA LANSIA - Apriani, Miftah; Musaddas, Rahmi (Jurnal Kesehatan Abdurrahman, 2024)
ABSTRACT Stroke is a cerebrovascular disease (brain blood vessels) which is characterized by impaired brain function due to damage or death of brain tissue due to reduced or blocked blood and oxygen flow to the brain. Objective: to determine the relationship between family knowledge and family support and the incidence of stroke in the elderly. This type of research uses an analytical survey method with a cross sectional approach. The sample in From the results of the analysis it was found that there was a significant relationship between this study amounting to 36 people using accidental sampling technique. From the results of the analysis it was found that there was a significant relationship between Family Knowledge (ρ-value=0.031), and family support (ρ-value=0.040), and the incidence of stroke in the elderly. Suggestion: provide health education for families regarding stroke, treatment, rehabilitation and care of stroke patients at home. Nurses are also expected to be able to help patients and families in increasing the patient's motivation to recover.